2021
DOI: 10.1542/hpeds.2021-006115
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Safety in Hospital Pediatrics During COVID-19: A National Qualitative Study

Abstract: OBJECTIVE: To describe challenges in inpatient pediatric quality and safety during the coronavirus disease 2019 (COVID-19) pandemic. METHODS: In a previous qualitative study, our team sought to broadly describe changes in pediatric inpatient care during the pandemic. For both that study and this ancillary analysis, we purposefully sampled participants from community and children’s hospitals in the 6 US states with the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…While many routine paediatric admissions were cancelled and there was a move to remote rather than in-person outpatient care,7 8 there was still a need to provide care for critically and chronically ill children requiring hospitalisation, including those with COVID-19 or paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) 9. In common with colleagues in adult settings, staff in children’s hospitals also had to adopt different working patterns, including redeployment both within and outside the hospital and delivery of care in new, often unfamiliar ways 10 11. A qualitative rapid appraisal of healthcare workers’ experiences and perceptions of delivering care to adults12 13 identified that structural conditions in the work environment, such as staffing levels, access to personal protective equipment (PPE) and ability to have adequate breaks, were key factors affecting well-being.…”
Section: Introductionmentioning
confidence: 99%
“…While many routine paediatric admissions were cancelled and there was a move to remote rather than in-person outpatient care,7 8 there was still a need to provide care for critically and chronically ill children requiring hospitalisation, including those with COVID-19 or paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) 9. In common with colleagues in adult settings, staff in children’s hospitals also had to adopt different working patterns, including redeployment both within and outside the hospital and delivery of care in new, often unfamiliar ways 10 11. A qualitative rapid appraisal of healthcare workers’ experiences and perceptions of delivering care to adults12 13 identified that structural conditions in the work environment, such as staffing levels, access to personal protective equipment (PPE) and ability to have adequate breaks, were key factors affecting well-being.…”
Section: Introductionmentioning
confidence: 99%